A Study on Individual Taxpayers Knowledge and Tax Compliance Intentions in Nepalese Tax System - Bidari, Dinesh; Khanal, Vishnu (Journal of Advanced Academic Research, 2026)
This paper explores how knowledge of taxes affects an individual taxpayer tax compliance intention within the Self-Assessment System (SAS) in Nepal through mixed methods and survey-based research topic. The research is determining the extent of tax knowledge of individual taxpayers under SAS and its correlation with the intentions of taxpayers to comply with taxation laws. This is done by using Likert-scale questionnaires on 90 tax payers, and interviewed 10 respondents of the Inland Revenue Office within Hetauda Sub metropolitan city. Qualitative data was gathered by use of face-to-face meetings as opposed to quantitative data being gathered using Google forms. JAMOVI is utilized in analysing quantitative data and qualitative data was analyzed thematically. Two hypotheses are examined H0: There are no differences of a significant level in the level of tax knowledge between taxpayers. H1: There is no significant association between tax knowledge and tax compliance intentions. The initial results showed a considerable diversity in the level of tax knowledge among various demographics, as well as the positive relationship between the level of higher tax knowledge and intentions to comply. In particular, very few business owners of small business in Hetauda Sub-Metropolitan city were knowledgeable of their tax compliance requirements (48.38) and 61.5% of the respondents indicated difficulties paying their taxes based on the difficult procedures and poor awareness exercises. Notwithstanding, 74.74% of the surveyed individuals indicated the relevance of being updated with the changing tax regulations in enhancing compliance. The alpha of the tool is determined as 0.85 and 0.83 under the Tax knowledge and Tax Compliance respectively indicating that the tool is reliable. The quantitative analysis also revealed that tax knowledge and compliance intentions were significantly positively related with the correlation coefficient (r) of 0.73 and p = 0.003 (p<0.05) was significant in residential income tax compliance in Nepal. These results explain why the need to increase the level of tax knowledge is of high importance to increase the level of tax compliance, and to the fact that better informed taxpayers tend to comply with their tax obligations. The research ends by stressing the necessity of specific learning programs to enhance the level of tax awareness among individual taxpayers in Nepal.